2016
DOI: 10.18632/aging.101110
|View full text |Cite
|
Sign up to set email alerts
|

Rpd3 interacts with insulin signaling in Drosophila longevity extension

Abstract: Histone deacetylase (HDAC) 1 regulates chromatin compaction and gene expression by removing acetyl groups from lysine residues within histones. HDAC1 affects a variety of processes including proliferation, development, metabolism, and cancer. Reduction or inhibition of Rpd3, yeast and flyHDAC1 orthologue, extends longevity. However, the mechanism of rpd3's effects on longevity remains unclear. Here we report an overlap between rpd3 and the Insulin/Insulin-like growth factor signaling (IIS) longevity pathways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…We have reported that rpd3 reduction increases resistance to hydrogen peroxide, but this resistance depends on fly age and sex. Resistance is higher in females compared to males, and more pronounced at older ages [ 18 ]. Increased resistance to paraquat is also observed in flies with heart-specific rpd3 reduction, as well as whole body reduction in 2 days old flies [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have reported that rpd3 reduction increases resistance to hydrogen peroxide, but this resistance depends on fly age and sex. Resistance is higher in females compared to males, and more pronounced at older ages [ 18 ]. Increased resistance to paraquat is also observed in flies with heart-specific rpd3 reduction, as well as whole body reduction in 2 days old flies [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…This reduced catabolism is related to the dietary restriction (DR) that extends lifespan in several species [39]. Also, it was recently reported that Rpd3 interacts partially with the insulin signaling pathway of the DR longevity mechanism [8,45].…”
Section: Discussionmentioning
confidence: 99%
“…However, systemic downregulation of Rpd3 extends lifespan [5,6], which is also observed in yeast with reduced Rpd3 expression [7]. Recently, it has been reported that Rpd3 interacts partially with the insulin signaling longevity pathway [8]. As several long-lived mutant flies display increased resistance to numerous stressors including oxidation, starvation, and heat compared to wild-type flies [9-12], Rpd3 downregulation also enhances stress resistance with extended lifespan [6].…”
Section: Introductionmentioning
confidence: 99%
“…Rpd3 is a zinc-dependent histone deacetylase in Drosophila and a homolog of mammal HDAC1. Reduction or inhibition of rpd3 extends longevity, increases energy storage and downregulates gene expressions of the IIS pathway [72]. There is an overlap between rpd3 and IIS longevity pathways, as mutations in rpd3 and dfoxo showed weakened stress resistance compared with rpd3 single mutant flies [72].…”
Section: Histone Modifications In Invertebrate Agingmentioning
confidence: 99%
“…Reduction or inhibition of rpd3 extends longevity, increases energy storage and downregulates gene expressions of the IIS pathway [72]. There is an overlap between rpd3 and IIS longevity pathways, as mutations in rpd3 and dfoxo showed weakened stress resistance compared with rpd3 single mutant flies [72]. Lifespan extension in rpd3 mutant flies may overlap with the mechanism of extension seen in dietary restriction (DR).…”
Section: Histone Modifications In Invertebrate Agingmentioning
confidence: 99%